Hubungan Antara Tingkat Kecemasan terhadap Prestasi Akademik pada Siswa SMA Kelas XII - Aprillia Ananda Putri; Wahyu Endang Setyowati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to examine the relationship between anxiety levels and academic achievement among twelfth-grade students at SMA Negeri 1 Mranggen. A correlational research design with a cross-sectional approach was employed, involving 298 students selected through purposive sampling. Data on anxiety levels and academic achievement were collected using validated questionnaires and school report scores, and analyzed using Chi-Square statistical tests. The results indicated that the majority of students experienced moderate anxiety, while a smaller proportion exhibited high or low anxiety levels. Academic achievement was predominantly in category C, followed by B, with few students attaining category A or D. Chi-Square analysis revealed a significant relationship between anxiety and academic performance (p < 0.001), suggesting that higher anxiety levels were associated with lower academic achievement, whereas lower anxiety levels corresponded to better performance. The findings highlight the critical role of anxiety management in supporting students’ learning outcomes and underscore the importance of psychological interventions to enhance academic success in high school settings.